PERANCANGAN APLIKASI INVENTORI BERBASIS WEB PADA TOKO ARLOJI PASAR BARU - Nelvin Jonathan; Desi Arisandi (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
The problem currently faced by Toko Arloji Pasar Baru is that the product data recording process is inefficient and ineffective because it is still done manually by writing in a logbook. This process takes considerable time due to the large volume of products. The common data recorded includes available products, incoming products, and outgoing products. A solution to address this problem is the design of a web-based inventory application. This web-based inventory application will be developed and will feature 14 different menus. The design of this inventory application aims to provide ease of use for users during the data recording process, reducing the time required and minimizing errors in data entry. The application will be used by both the owner and staff of Toko Arloji Pasar Baru. The development process will follow the SDLC methodology, specifically the waterfall model. The programming languages used for the design and development of the application are HTML, PHP, CSS, and Javascript, with the Bootstrap framework and MySQL as the database.